Kajian Sosiologis dan Antropologis Terhadap Konflik Tanah dan Perlindungan Masyarakat Hukum Adat yang Terdampak Pembangunan Proyek Strategis Nasional (Studi Kasus: Masyarakat Adat Yei Kian, Papua) - Hakeem, Mirza Athaya Ghaisan; Widianto, Alif Putra (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The construction of National Strategic Projects (NSP) often raises conflicts with customary law communities regarding the possession and utilization of ulayat lands. The case of the indigenous people of Yei Kian in Papua is a tangible example of the tension between the interests of national development and the traditional rights of indigenous peoples. This study aims to analyze the forms of legal protection towards the customary law community of Yei Kian affected by PSN as well as evaluate the compatibility of the PSN policy with the principle of recognition and protection of customary law community as regulated in Article 18B paragraph (2) of the 1945 Constitution Tahundang Tentang Undang-Undang Environmental Protection and Management. The research method used is normative law, with a legislative and conceptual approach, analyzing the foundations of law, legal systematics, as well as related literature. The results of the study show that the legal protection of the Yei Kian community is still formal in nature and has not been adequate, both from a sociological and anthropological perspective. The processes of recognition of ulayat rights, the implementation of Free, Prior, and Informed Consent (FPIC), as well as participation in Analysis Regarding Environmental Impacts (AMDAL) are often merely administrative in nature without respect for the social structures, cultural values, and cultural meanings of customary lands. As a result, PSN policies have not fully aligned with the principles of recognition and protection of customary law communities. This study concludes that effective legal protection of the Yei Kian community must be multidimensional in nature, integrating formal recognition, meaningful participatory procedures, and socio-cultural restitution. Development policies are needed that are inclusive, respect traditional rights, and safeguard the social, cultural, as well as ecological sustainability of indigenous peoples.